Changes in posttraumatic growth, core belief disruption, and social support over the first year of the COVID-19 pandemic - Dominick, Whitney (Frontiers in Psychology, 2022)
Posttraumatic Growth (PTG) is the positive psychological change that may occur after a highly stressful situation that shakes a person’s core beliefs about the world. During 2020, the United States experienced the COVID-19 pandemic and a highly contentious political election, both of which have the potential to disrupt core beliefs and evoke perceptions of PTG. Posttraumatic growth, core belief disruption, perceived social support from humans and pets, coping strategies, and stressful events were assessed in 201 participants from the United States (Mage: 35.39, SD: 14.60) at four time points from April 2020 (T1) until April 2021 (T4). While total PTG did not significantly change from Time 1 to Time 4, perceptions of personal strength and new possibilities increased, as did core belief disruption, and use of coping strategies decreased. Higher PTG was reported by those who owned pets, those who knew someone who had been hospitalized due to COVID-19, and those who knew someone who had died of COVID-19. While rating COVID-19 or politics as the most stressful event at Time 4 did not correspond to differences in PTG, those who perceived the event to be resolved had higher PTG than those who perceived the event to be ongoing. Having COVID-19 personally and vaccination status was not associated with differences in Posttraumatic Growth. PTG at Time 4 was predicted by core belief disruption and social support in the full sample and in the pet owners only sample, and by support from video conferencing for the full sample only. Time 4 PTG was also predicted by core belief disruption, problem-focused coping, and avoidance coping. Results are discussed in terms of the PTG theoretical model. Additionally, implications for interventions aimed at fostering psychological growth, including through non-traditional forms of social support (i.e., remote communication and perceived support from pets) are addressed.